A Sexism Analysis in English Textbook Used in Indonesian Schools' 7th Grade Entitled: “When English Rings a Bell” Published By the Ministry of Education and Culture - Suryawati, Sri Suci; Kholid, M Ridho; Tipani, Ayu (Universitas Islam Negeri Raden Intan Lampung, 2023)
Sexism is a foundation where there is unequal treatment between men and women in society. This unequal treatment emphasizes the dominance of men over women. This research analyzed sexism in English textbook 7th grade entitled “When English Rings a Bell” Published by the Ministry of Education and Culture at Indonesia. This research used descriptive qualitative method and used six criteria of sexism based on NCTE guidelines for gender-fair use of language and also Porreca’s study to analyze the data, that are includes: generic he, generic man, titles, labels and names, occupational roles, omission, firstness. The technique of data analysis of this research adopted from Miles and Huberman theory. The aims of this research is to know the dominant criteria of sexism found in English textbook 7th grade entitled “When English Rings a Bell” Published by Ministry of Education and Culture at Indonesia. The results of this research shows that there are 5 criteria of sexism found in the English textbook 7th grade entitled “When English Rings a Bell” Published by Ministry of Education and Culture at Indonesia, that are includes: generic man, titles, labels and names, the occupational, omission, firstness. The dominant criteria’s of sexism found is omission criteria. Key words: EFL textbook, sexism, society